Heavy quark potential and LQCD based quark condensate at finite magnetic field - Nilima, Indrani; Bandyopadhyay, Aritra; Ghosh, Ritesh; Ghosh, Sabyasachi (The European physical journal. C, Particles and fields, 2023)
In the present work, we have studied heavy quarkonia potential in hot and magnetized quark gluon plasma. Inverse magnetic catalysis (IMC) effect is incorporated within the system through the magnetic field modified Debye mass by modifying the effective quark masses. We have obtained the real and imaginary part of the heavy quark potential in this new scenario. After the evaluation of the binding energy and the decay width we comment about the dissociation temperatures of the heavy quarkonia in presence of magnetic field.
Gesehen am 14.06.2023
Published online: 17 January 2023